Entanglement of southern elephant seals in squid fishing gear - Campagna, Claudio; Falabella, Valeria; Lewis, Mirtha Noemi (Marine Mammal Science)
Although southern elephant seals, Mirounga leonina, prey upon fish and squid species that are targeted by large commercial operations that overlap with their foraging range (Daneri and Carlini 2002, van den Hoff et al. 2002, Bradshaw et al. 2003 and references therein), direct interactions with fisheries have not been widely reported. Most of the available evidence concerns interaction with fisheries targeting toothfish, Dissostichus spp. (Slip 1995, McMahon et al. 2000, van den Hoff et al. 2002, Hindell et al. 2003). We report on the entanglement of southern elephant seals from coastal Patagonia, Argentina, in squid fishing gear (Fig. 1). To our knowledge, this is the first description of a direct interaction of a squid commercial fishery with southern elephant seals. Fil: Campagna, Claudio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina. Wildlife Conservation Society; Estados Unidos Fil: Falabella, Valeria. Wildlife Conservation Society; Estados Unidos Fil: Lewis, Mirtha Noemi. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina